1991
DOI: 10.2527/1991.69103908x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of real-time ultrasound and other live measures to carcass measures as predictors of beef cow energy stores

Abstract: Thirty-nine mature cows were divided into three condition groups on the basis of their subcutaneous fat thickness as determined by real-time ultrasound. A representative animal from each group was measured and slaughtered. The remaining cows with each group were stratified evenly into two groups with one group fed to gain weight and the other to lose weight. Several ultrasound and other live measures were taken every 4 wk and two animals per subgroup were randomly slaughtered. Carcass data were collected and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
9

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
2
12
1
9
Order By: Relevance
“…However, higher correlation coefficients between carcass and ultrasound measurement of the 12th rib (SBT and SF 12 ) were shown by Bullock et al (1991; Tables 3 and 4), in accordance with the results from Greiner et al (2003) study. Some studies reported an average absolute low difference between ultrasound and carcass measurement in the 12th rib fat (SBT and SF 12 ) for steers, such as 0.16 cm (Greiner et al, 2003) and 0.19 cm (Brethour, 1992).…”
Section: Animal Live Recording Characteristicssupporting
confidence: 87%
“…However, higher correlation coefficients between carcass and ultrasound measurement of the 12th rib (SBT and SF 12 ) were shown by Bullock et al (1991; Tables 3 and 4), in accordance with the results from Greiner et al (2003) study. Some studies reported an average absolute low difference between ultrasound and carcass measurement in the 12th rib fat (SBT and SF 12 ) for steers, such as 0.16 cm (Greiner et al, 2003) and 0.19 cm (Brethour, 1992).…”
Section: Animal Live Recording Characteristicssupporting
confidence: 87%
“…That syllogism has been validated in young animals with carcass dissection (Greiner et al, 2003a;Tait et al, 2005) but has not been widely explored in mature cows. Bullock et al (1991) confirmed that ultrasound adds value to BCS for predicting cow composition. Consistency across repeated scans of the same cows has not been considered.…”
Section: Introductionmentioning
confidence: 61%
“…The predicted values were accurate (4±4% lower and 1±5% higher than actual values in PA and PI cows, respectively). In this regard, BCS has been proved the best predictor of total amount of body subcutaneous fat when measured after slaughter in beef (R 2 =0.77) (Bullock et al, 1991) and dairy cows (R 2 =0.36-0.65) (Domecq et al, 1995).…”
Section: Discussion Live Animal Traits (Experiments 1 and 2)mentioning
confidence: 98%